TRADISI BAAYUN MULUD DI KOTA BANJARMASIN (KAJIAN FENOMENOLOGIS) - Arni, Arni; Maimanah, Maimanah; Norhidayat, Norhidayat (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
Banjarese people carry out the celebration or commemoration of the birthday of Prophet Muhammad Saw. with swinging children or adults, this event commonly referred to baayun mulud. The purpose of this event is based on various motives, both religious, sociological, and some other political-cultural motives. The religious motivation is the belief that it will be granted all the luck, get blessings, health, safety, recover from illness, child is not naughty / fussy and because nadzar which granted Allah Swt. The sociological motivation of this event is to cultivate the spirit of togetherness, mutually cooperation, and unity in the midst of urban society that tends to be individualist today. While the political-cultural motivation can be felt from the statement of the organizing committee who firmly stated that this event was held in order to revive a tradition that has been forgotten, whereas it used to exist in the time of the Sultanate of Banjar. Along with the reaffirmation of the existence of the Sultanate of Banjar, then the existence of culture that ever existed in the heyday of this Sultanate also tried to be raised again.